NSEM: Duygu Analizi için Özgün Yıǧınlanmiş Topluluk Yöntemi - Işik, Yunus Emre; Görmez, Yasin; Kaynar, Oǧuz; Aydin, Zafer; Emre Isik, Yunus (Institute of Electrical and Electronics Engineers Inc., 2018)
Today, people often share their ideas, opinions and feelings through forums, social media sites, blogs and similar platforms. For this reason, access to these data has become very easy. Increase in the number of shares makes it possible to analyze and use these data in terms of marketing and politics. However, due to the large number of data, it is impossible that this analysis will be done by humans. Determination of what type of emotion is included automatically is done by sentiment analysis methods. In these methods, the text is defined as a mathematical vector and classified by machine learning methods. Ensemble methods are one of the most important methods used as classifiers in sentiment analysis. In these methods, a classifier error is tried to be solved by another classifier. In sentiment analysis, the feature vector that describes the text is as important as the classifier. Feature vectors obtained using different methods can make mistakes in different places. For this reason, in this study, NSEM is proposed for sentiment analysis, which is a new ensemble method that uses 2 different classifiers and 2 different feature extraction methods. As a result of the analysis, the proposed method is the most successful method with an accuracy rate of 79.1%. © 2019 Elsevier B.V., All rights reserved.
NSEM: Novel Stacked Ensemble Method for Sentiment Analysis
Keywords: Ensemble Method; Machine Learning; Sentiment Analysis; Stacked Ensemble Methods; Data Handling; Data Mining; Learning Systems; Machine Learning; Sentiment Analysis; Accuracy Rate; Ensemble Methods; Feature Extraction Methods; Feature Vectors; Machine Learning Methods; Number of Datum; Social Media; Classification (Of Information)